(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The role of the penitentiary system in the social adaptation of persons released from correctional institutions is very great. Before discussing its important aspect, it is appropriate to briefly explain its content.